VALIDITY AND REPRODUCIBILITY OF MEASURING THE KINEMATIC COUPLING BEHAVIOR OF CALCANEAL PRONATION/SUPINATION AND SHANK ROTATION DURING WEIGHT BEARING USING AN OPTICAL THREE-DIMENSIONAL MOTION ANALYSIS SYSTEM (International Journal of Physiotherapy, 2017)
Background: It’s important to understand the kinematic coupling of calcaneus and shank to optimize the pathological movement of the lower extremity. However, the quantitative indicator to show the kinematic coupling hasn’t been clarified. We measured the angles of calcaneal pronation-to-supination and shank rotation during pronation and supination of both feet in standing position and devised a technique to quantify the kinematic coupling behavior of calcaneal pronation/supination and shank rotation as the linear regression coefficient (kinematic chain ratio: KCR) of those measurements. Therefore, we verified the validity and reproducibility of this technique.Methods: This study is a non-comparative cross-sectional study. The KCR, which is an outcome, was measured using an optical three-dimensional motion analysis system in 10 healthy subjects. The coefficient of determination (R²) was calculated for the linear regression equation of the angle of calcaneal pronation-to-supination and angle of shank rotation, and the intraclass correlation coefficient (ICC [1,1]) was calculated for the KCR during foot pronation and foot supination and for the KCR measured on different days. And also, skin movement artifacts were investigated by measurement of the displacement of bone and body surface markers in one healthy subject.Results: The linear regression equation of calcaneal pronation/supination and the angle of shank rotation included R²≥0.9 for all subjects. The KCR on foot pronation and supination had an ICC(1,1) of 0.95. The KCR measured on different days had an ICC(1,1) of 0.72. Skin movement artifacts were within the allowable range.Conclusion: The validity and reproducibility of this technique were largely good, and the technique can be used to quantify kinematic coupling behavior.